Subdural collections due to non-typhi Salmonella infections in two Malaysian children. - Ismail , Intan Hakimah; Othman, Norlijah; C. D., Zubaidah; Ahmad, Norazah (Singapore Medical Association, 2008)
Subdural collections caused by Salmonella infection are rarely encountered in children. We present two cases caused by non-typhi Salmonella, one a four-and-a-half-month-old boy presenting with subdural effusion, and the other, a 16-month-old boy with empyema. The diagnosis was confirmed on blood and subdural pus cultures. One patient had status epilepticus following focal fit, and the other had prolonged fever without any localising signs of infection on admission. They responded well to prompt surgical drainage and prolonged systemic antibiotic therapy. Contrary to previous reports, both patients showed favourable outcome in terms of neurological sequelae